Phase Transformation on Two-Dimensional MoTe2 Films for Surface-Enhanced Raman Spectroscopy - Caiye Zhao; Junwen Huang (Molecules)
Two-dimensional (2D) transition metal dichalcogenides (TMDs) have recently become attractive candidate substrates for surface-enhanced Raman spectroscopy (SERS) owing to their atomically flat surfaces and adjustable electronic properties. Herein, large-scale 2D 1T′- and 2H-MoTe2 films were prepared using a chemical vapor deposition method. We found that phase structure plays an important role in the enhancement of the SERS performances of MoTe2 films. 1T′-MoTe2 films showed a strong SERS effect with a detection limit of 1 × 10−9 M for the R6G molecule, which is one order of magnitude lower than that of 2H-MoTe2 films. We demonstrated that the SERS sensitivity of MoTe2 films is derived from the efficient photoinduced charge transfer process between MoTe2 and adsorbed molecules. Moreover, a prohibited fish drug could be detected by using 1T′-MoTe2 films as SERS substrates. Our study paves the way to the development and application of high-performance SERS substrates based on TMD phase engineering.